Urinary Bladder, Cystitis and Nerve/Urothelial Interactions - Birder, Lori A. (2013)
A hallmark of functional pain syndromes, such as bladder pain syndrome/interstitial cystitis (BPS/IC) is pain in the absence of demonstrable infection or pathology of the viscera or associated nerves. There are no clear definitions of this syndrome, no proven etiologies and no effective treatments able to eradicate the symptoms. This condition is characterized by suprapubic pain, associated with bladder filling and can also be accompanied by a persistent strong desire to void, increased frequency of urination and nocturia. Severe cases of this disorder, which affects primarily women, can have considerable impact on the quality of life of patients due to extreme pain and urinary frequency, which are often difficult to treat. In addition, BPS/IC patients may also suffer co-morbid conditions where pain is a common symptom (such as irritable bowel syndrome, fibromyalgia). Theories explaining the pathology of bladder pain syndrome are many and include an altered bladder lining and possible contribution of a bacterial agent.